Giardiasis in children living in post-earthquake camps from Armenia (Colombia) - Gonzalez Maria; Torres Elizabeth; Gallego Martha; Loango Nelsy; Marin-Vasquez Carolina; Lora-Suarez Fabiana; Castaño-Osorio Jhon; Gómez-Marín Jorge (BMC, 2002)
Abstract Background An earthquake in the coffee growing region of Colombia on January 25, 1999 destroyed 70% of the houses in Armenia city. Transitory housing camps still remained until two years after the disaster. Parasitological studies found that, in this population, giardiasis was the most frequent parasitic infection. This study was carried out in order to determine the epidemiological risk factors associated with this high prevalence. Methods Fecal samples were obtained from 217 children aged between 3 and 13 years. Stool samples were studied by direct wet examination and stained with ferric hematoxilin for microscopical examination. Epidemiological data were collected by questionnaire and analyzed by using the Epi-info software (CDC, Atlanta 2001). Results Giardia cysts were observed in 60.4% of the samples presented and trophozoites in 4.6%. The following epidemiological and laboratory factors were significantly associated with Giardia infection: 1. Use of communal toilet (vs. individual toilet) OR: 3.9, CI95%: 1.2-16; 2. water provision by municipal ducts (vs. water provision by individual tanks) OR: 3.5, CI95% 1.1-14, and 3. presence of mucus in stool OR: 2.3, IC95%: 0.9-6.7. Conclusions A high prevalence of giardiasis was found in children living in temporary houses after the 1999 earthquake in Armenia (Colombia). Giardiasis is an emerging disease in post-disaster situations and adequate prevention measures should be implemented during these circumstances.